The Challenges of a Judicial Employment Contracting Approach in Fiji - Peni Sikivou; Subhash Appana; Auta Moceisuva (Asia-Pacific Journal of Public Policy, 2023)
This study examines the Government of Fiji's new public management (NPM) employment contracting system and its legal challenges. The article raises the question of whether Section 97 of Fiji's 2013 Constitution of the courts and all judicial officers being independent of the legislative and executive branches of government and the law is applied without fear, favor, or bias, is guaranteed under a contracting mode of employment for judicial officials. This paper investigates whether three-year performance contracts ensure the independence of Fiji's judiciary. After extensive analysis, the authors propose that permanent tenure provides greater protections for Fiji's magistrate court judges, high court judges, and judicial officials by allowing them to exercise their independent roles as stipulated in Section 97 of the 2013 Fiji Constitution.